Hydrogen‐bond landscapes, geometry and energetics of squaric acid and its mono‐ and dianions: a Cambridge Structural Database, IsoStar and computational study. Issue 5 (26th February 2016) - Allen, Frank H.; Cruz‐Cabeza, Aurora J.; Wood, Peter A.; Bardwell, David A.
Abstract : As part of a programme of work to extend central‐group coverage in the Cambridge Crystallographic Data Centre's (CCDC) IsoStar knowledge base of intermolecular interactions, we have studied the hydrogen‐bonding abilities of squaric acid (H2 SQ) and its mono‐ and dianions (HSQ − and SQ 2− ) using the Cambridge Structural Database (CSD) along with dispersion‐corrected density functional theory (DFT‐D) calculations for a range of hydrogen‐bonded dimers. The —OH and —C=O groups of H2 SQ, HSQ − and SQ 2− are potent donors and acceptors, as indicated by their hydrogen‐bond geometries in available crystal structures in the CSD, and by the attractive energies calculated for their dimers with acetone and methanol, which were used as model acceptors and donors. The two anions have sufficient examples in the CSD for their addition as new central groups in IsoStar. It is also shown that charge‐ and resonance‐assisted hydrogen bonds involving H2 SQ and HSQ − are similar in strength to those made by carboxylate COO − acceptors, while hydrogen bonds made by the dianion SQ 2− are somewhat stronger. The study reinforces the value of squaric acid and its anions as cocrystal formers and their actual and potential importance as isosteric replacements for carboxylic acid and carboxylate functions.